THE INFLUENCE OF SHARIA COMPLAINCE AGAINST FRAUD ON THE SHARIA BANKS IN INDONESIA - Santika, Ana; Ghofur, Ruslan Abdul (Islamic Economics Program, Faculty of Islamic Economics and Business, 2019)
This study aims to analyze how big the influence of sharia compliance towards the profitability of Islamic Banks in Indonesia. The sample selected by the method of purposive sampling so obtained 9 samples of islamic banks The Unit of analysis in the study amounted to 45 of the annual report of Islamic Banks. Research approach with quantitative methods using secondary data. Type the quantitative data in the form of data of financial statements (annual report) each bank of the the year 2013 until 2017. The results of this study seen from the results of the F test, a variable Profit Sharing Ratio (PSR), Islamic Income Ratio (IsIR), and Islamic Investment Ratio (IIR) simultaneously no significant effect on the variable fraud. From the results of t test variable Profit Sharing Ratio (PSR), Islamic Income Ratio (IsIR), and no significant effect on the variable fraud. From the results of t test variable Profit Sharing Ratio (PSR), Islamic Income Ratio (IsIR), and Islamic Investment Ratio (IIR) no effect and not significant on the variable fraud. Based on the results of the above analysis in the absence of such influence caused, the activities in Islamic banking are currently carrying out compliance on sharia principles, because the lower the level of fraud the higher the level of shariah compliance on Islamic banking. The banks still have to improve the level of compliance with the principles of sharia and also do activities to the prevention of fraud.